An Empirical Case Study of DEMATEL Method Focus on Calculating the Students Organization Improvement in POLITALA - Titik Wijayati; Mufrida Zein; Muhammad Ghalih; Muhammad Fajar (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2021)
The single-mindedness of this study is to find the key factors prompting the Students Organization Improvement and explore the causal relationships between perspectives (P) and criteria (C). This case study used Decision-Making Trial and Evaluation Laboratory (DEMATEL) method used for making decisions and analyses to forecast future scenarios. The results found that the DEMATEL include six main perspectives and eighteen criteria were extracted and then validated by fifteen experts. Therefore, the most critical evaluation perspective with the most exceptional value was 11.4074, although Availability (P4) was the least essential perspective with the smallest value 7.0138. Regarding value, the prioritization of the importance of four evaluation perspectives numbered from perspectives P1 to perspectives P4. Finally, the proposed methods not only improve the DEMATEL methodology but also provide a valuable reference to do the best planning for Calculating the Students Organization Improvement in POLITALA.